The Role Of Character Education In Forming Ethical And Responsible Students - Tiara Ramadhani; Danar Widiyanta; Yena Sumayana; Rengga Yudha Santoso; Puspita Dian Agustin; Al-Amin (IJGIE (International Journal of Graduate of Islamic Education), 2024)
Character education refers to an approach to learning that aims to help students develop moral and ethical values, such as honesty, responsibility and empathy. The integration of these values in the curriculum and school activities along with the active support of teachers, families and communities are the main efforts for character education to build individuals who are highly ethical and responsible in every aspect of their lives. In this study, the literature research method was used. From the results, it is evident that teachers who have undergone specialised training in character education play an important role as living examples of these values. In addition, a safe and supportive school environment greatly contributes to the ethical formation of students. Another opinion states that the active participation of parents and the community also strengthens the implementation of moral values in schools through their daily behaviour. This finding proves the synergy relationship between the collaborative participation of the main institutions, namely school, family and the wider community, can empower students with strong character, have good morals and be perfectly responsible.